Perlindungan Hukum Terhadap Hak-Hak Masyarakat Adat Di Kabupaten Pelalawan Terkait Dengan Penerbitan Ijin Lahan - Maryati Bachtiar; Riska Fitriani (Jurnal Media Hukum, 2017)
Overlap the land permit granted by the Government of Pelalawan result of indigenous people communal land taken without regard to the rights of the local population. In issuing licenses, many customary rights of indigenous peoples are disadvantaged. Because in practice the country has not fully provide legal protection of the rights of indigenous peoples, as in the case of customary land disputes and conflicts/communal, indigenous peoples still in a weak position associated with the policies issued by the state. Need for Local Regulation in Pelalawan governing the legal protection of the rights of indigenous peoples, so that indigenous land disputes and conflicts/customary in Pelalawan can be minimized.